Analytical mechanisms for determining key investment priorities in the construction sector - TUGAY, Oleksiy; OSIPOV, Oleksandr; EMELIANOVA, Olena; DEMYDOVA, Olena (Ways to Improve Construction Efficiency, 2025)
This article explores the analytical mechanisms used to determine key investment priorities in the construction sector. Given the growing challenges in urbanization, environmental sustainability, and digital transformation, effective management of investment resources has become a critical task. The study analyzes modern approaches to evaluating investment projects, including multi-criteria analysis methods, economic-mathematical modeling, and forecasting. Special attention is given to the application of artificial intelligence, big data, and geoinformation systems in investment decision-making processes. The use of these technologies enhances forecast accuracy, reduces investment risks, and optimizes financial flow management. Additionally, the study examines risk factors, including macroeconomic fluctuations, volatility in the construction materials market, and changes in regulatory frameworks. The article also reviews methods for assessing investment efficiency, particularly discounted cash flow (DCF), net present value (NPV) analysis, internal rate of return (IRR), and other financial instruments that help determine the feasibility of investments in construction projects. A separate section is dedicated to analyzing environmental and social criteria for investment evaluation, which are crucial in the context of sustainable development. The role of government regulation, financial instruments, and investment support programs in the construction sector is also considered. A conceptual model for evaluating investment priority areas is proposed, integrating economic, social, and environmental factors. The research findings may be useful for government agencies, investors, and construction sector companies in developing growth strategies and effectively allocating financial resources. The application of the proposed methods will enhance the competitiveness of the construction industry, ensure real estate market stability, and facilitate the implementation of innovative solutions in construction processes. The proposed approach to determining investment priorities enables a comprehensive assessment of project potential, considering financial, technological, environmental, and market factors. This contributes to the efficient use of capital, risk minimization, and overall improvement in the effectiveness of the construction sector.